التوافق النفسي وعلاقته بالدافعية للتعلم لدى تلاميذ سنة أولى ثانوي - بابة، فاطمة, بن خليفة، فاطمة الزهرة (جامعة الوادي university of Eloued, 2021)
الملخص: يتناول موضوع الدراسة التوافق النفسي وعلاقته بالدافعية للتعلم لدى تلاميذ سنة أولى ثانوي، باعتبار هذه المرحلة العمرية أكثر حساسية وتأثير على نفسية الطالب . 1.الإشكاليات : - هل توجد علاقة ذات دلالة احصائية بين التوافق النفسي و أبعاده والدافعية للعلم لدى تلاميذ سنة أولى ثانوي؟ - هل توجد فروق ذات دلالة احصائية بين الذكور والإناث في مقياس التوافق النفسي لدى تلاميذ سنة أولى ثانوي؟ - هل توجد فروق ذات دلالة احصائية بين الذكور والإناث في مقياس الدافعية للتعلم لدى تلاميذ سنة أولى ثانوي؟ 2. الفرضيات : بالنظر إلى الدراسات السابقة والإطار النظري للدراسة الحالية وأهدافها أمكننا من صياغة فرضيات الدراسة على النحو التالي: - توجد علاقة ذات دلالة احصائية بين التوافق النفسي وأبعاده والدافعية للتعلم لدى تلاميذ سنة أولى ثانوي. - لاتوجد فروق دالة احصائيا بين الذكور والإناث في مقياس التوافق النفسي لدى تلاميذ سنة أولى ثانوي. - لاتوجد فروق دالة احصائيا بين الذكور والإناث في مقياس الدافعية للتعلم لدى تلاميذ سنة أولى ثانوي. 3. أهداف الدراسة : الموضوع هو عبارة عن بحث ميداني قامت به الطالبتان لتحقيق أهداف نذكر منها: - دراسة علاقة التوافق النفسي بالدافعية للتعلم لدى أفراد العينة. - دراسة الفروق بين كل من مقياس التوافق النفسي ومقياس الدافعية للتعلم لدى أفراد العينة في ظل متغير الجنس. 4. منهج وأدوات الدراسة : - اعتمدنا على استخدام المنهج الوصفي الارتباطي المقارن، كما استخدمنا استبيان كأداة لجمع البيانات والمتمثل في مقياس التوافق النفسي " زينب محمود شقير" ومقياس الدافعية للتعلم " ليوسف قطامي" . 5. عينة الدراسة: - تم اجراء الدراسة على (79) تلميذ وتلميذة من تلاميذ سنة أولى ثانوي، ثانوية الشهيد ساسي رضواني بالرقيبة – ولاية الوادي- ، وقد اخترنا العينة بطريقة عشوائية . 6. نتائج الدراسة : - توصلنا في هذه الدراسة إلى مجموعة من النتائج نلخصها في النقاط التالية : - وجود علاقة ذات دلالة احصائية بين التوافق النفسي والدافعية للتعلم لدى تلاميذ سنة أولى ثانوي. - وجود علاقة ذات دلالة احصائية بين أبعاد التوافق النفسي والدافعية للتعلم لدى تلاميذ سنة أولى ثانوي. - لاتوجد فروق ذات دلالة احصائية بين الذكور والإناث في مقياس التوافق النفسي لدى تلاميذ سنة أولى ثانوي. - توجد فروق ذات دلالة احصائية بين الذكور والإناث في مقياس الدافعية للتعلم لدى تلاميذ سنة أولى ثانوي . summary : انجليزية The subject of the study deals with psychological adjustment and its relationship to the motivation to learn among first year secondary students, given that this age stage is more sensitive and affects the student’s psyche. 1. Problems: - Is there a statistically significant relationship between psychological adjustment and its dimensions and motivation for science among first year secondary students? - Are there statistically significant differences between males and females in the psychological adjustment scale for first year secondary students? - Are there statistically significant differences between males and females in the measure of motivation to learn among first year secondary students? 2. Hypotheses: Looking at the previous studies and the theoretical framework of the current study and its objectives, we were able to formulate the study hypotheses as follows: - There is a statistically significant relationship between psychological adjustment and its dimensions and motivation to learn among first year secondary students. - There are no statistically significant differences between males and females in the psychological adjustment scale for first year secondary students. - There are no statistically significant differences between males and females in the learning motivation scale for first year secondary students. 3. Study objectives: The topic is a field research carried out by the two students to achieve goals, including: - Studying the relationship between psychological adjustment and motivation to learn among the sample members. - Studying the differences between each of the psychological adjustment scale and the learning motivation scale among the sample members in light of the gender variable. 4. Study method and tools: - We relied on the use of the comparative correlative descriptive approach, and we also used a questionnaire as a tool for data collection, which is represented in the psychological compatibility scale "Zainab Mahmoud Shukair" and the learning motivation scale "Youssef Qatami". 5. Study sample: - The study was conducted on (79) male and female students of the first year of secondary school, Martyr Sassi Radwani High School in Raqiba - El Wadi State -, and we chose the sample randomly. 6. Study results: In this study, we reached a set of results, which are summarized in the following points: - There is a statistically significant relationship between psychological adjustment and motivation to learn among first year secondary students. - There is a statistically significant relationship between the dimensions of psychological adjustment and motivation to learn among first year secondary students. - There are no statistically significant differences between males and females in the psychological adjustment scale for first year secondary students. There are statistically significant differences between males and females in the scale
مذكرة ماستر علم النفس تخصص علم النفس المدرسي
Keywords: التوافق النفسي، الدافعية للتعلم; Compatibilité psychologique, motivation à apprendre; Psychological compatibility, motivation to learn